The Diagnosing Challenge of a Positive ANCA Vasculitis in the Paediatric Age - Clara Preto; Armandina Silva; Sandra Alves; Margarida Guedes; Paula Matos; Conceição Mota; Paula Rocha; Paula C. Fernandes (Case Reports in Pediatrics)
ANCA-positive systemic vasculitides, rare in paediatric age, present multiorganic involvement. A female teenager presented with a history of subglottic stenosis diagnosed at the age of 12. From the investigation carried out, we highlight hematoproteinuria and negative ANCAs. At 15 years old, she was admitted for gastrointestinal symptoms and respiratory distress. She presented poor peripheral perfusion, pulmonary haemorrhage, respiratory failure, and severe renal insufficiency. She was started mechanical ventilation and emergency haemodialysis. The immunological study revealed ANCA MPO positive. A presumptive diagnosis of ANCA-positive vasculitis was made, and she was started corticotherapy, cyclophosphamide, and plasmapheresis. A renal biopsy, performed later, showed crescentic glomerulonephritis with chronicity signs. Positive ANCA vasculitis may progress slowly or suddenly. The diagnosis was confirmed by a biopsy; however, we can make a presumptive diagnosis based on clinical findings and in a positive ANCA test in order to start an early treatment and decrease the associated morbimortality.